Between Motherhood and Violence: Women's Labor Challenges in Mexico - Juárez García, Julia; Cruz Díaz, Felipe (Convergencia Revista de Ciencias Sociales, 2026)
In Mexico, cultural norms reinforcing male dominance limit women's economic and physical autonomy. This study examines how the motherhood penalty and gender-based violence restrict income opportunities and increase vulnerability. Using state-level data from 2005 to 2023, findings show that motherhood reduces earnings, especially as the number of children increases. Moreover, between 2015 and 2023, efforts to close the gender income gap coincided with rising feminicides, signaling a backlash against successful women. The results emphasize that addressing the social structures perpetuating gender inequality is essential. Entrepreneurship emerges as a viable option for women seeking autonomy, though challenges like limited financing and machismo persist. Comprehensive policies are needed to support women.